Catalytic Transfer Hydrogenation Using Biomass as Hydrogen Source. Issue 13 (22nd August 2018) - Manna, Srimanta; Antonchick, Andrey P.
Abstract: We developed an operationally simple method for the direct use of biomass‐derived chemical entities in a fundamentally important process, such as hydrogenation. Various carbohydrates, starch, and lignin were used for stereoselective hydrogenation. Employing a transition metal catalyst and a novel catalytic system, the reduction of alkynes, alkenes, and carbonyl groups with high yields was demonstrated. The regioselective hydrogenation to access different stereoisomers was established by simple variations in the reaction conditions. This work is based on an unprecedented catalytic system and represents a straightforward application of biomass as a reducing reagent in chemical reactions. Abstract : Sweet chemistry . A catalytic transfer hydrogenation using biomass‐derived carbohydrates as reagent is developed. Stereoselective and chemoselective hydrogenation of alkynes, alkenes, and carbonyl compounds is demonstrated. This work provides an operationally simple method for transfer hydrogenation and represents a new concept for the application of renewable biomass.